Handbook of fluorescence spectroscopy and imaging : - Sauer, Markus (Wiley-VCH, 2011)
Providing much-needed information on fluorescence spectroscopy and microscopy, this ready reference covers detection techniques, data registration, and the use of spectroscopic tools, as well as new techniques for improving the resolution of optical microscopy below the resolution gap. Starting with the basic principles, the book goes on to treat fluorophores and labeling, single-molecule fluorescence spectroscopy and enzymatics, as well as excited state energy transfer, and super-resolution fluorescence imaging.